Identification of ALEKSIN as a novel multi-IRF inhibitor of IRF- and STAT-mediated transcription in vascular inflammation and atherosclerosis - Antonczyk, Aleksandra; Kluzek, Katarzyna; Herbich, Natalia; Boroujeni, Mahdi Eskandarian; Krist, Bart; Wronka, Dorota; Karlik, Anna; Przybyl, Lukasz; Plewinski, Adam; Wesoly, Joanna; Bluyssen, Hans A. R. (Frontiers in Pharmacology, 2025)
Cardiovascular diseases (CVDs) include atherosclerosis, which is an inflammatory disease of large and medium vessels that leads to atherosclerotic plaque formation. The key factors contributing to the onset and progression of atherosclerosis include the pro-inflammatory cytokines interferon (IFN)α and IFNγ and the pattern recognition receptor (PRR) Toll-like receptor 4 (TLR4). Together, they trigger the activation of IFN regulatory factors (IRFs) and signal transducer and activator of transcription (STAT)s. Based on their promoting role in atherosclerosis, we hypothesized that the inhibition of pro-inflammatory target gene expression through multi-IRF inhibitors may be a promising strategy to treat CVDs. Using comparative in silico docking of multiple IRF–DNA-binding domain (DBD) models on a multi-million natural compound library, we identified the novel multi-IRF inhibitor, ALEKSIN. This compound targets the DBD of IRF1, IRF2, and IRF8 with the same affinity and simultaneously inhibits the expression of multiple IRF target genes in human microvascular endothelial cells (HMECs) in response to IIFNα and IFNγ. Under the same conditions, ALEKSIN also inhibited the phosphorylation of STATs, potentially through low-affinity STAT-SH2 binding but with lower potency than the known multi-STAT inhibitor STATTIC. This was in line with the common inhibition of ALEKSIN and STATTIC observed on the genome-wide expression of pro-inflammatory IRF/STAT/NF-κB target genes, as well as on the migration of HMECs. Finally, we identified a novel signature of 46 ALEKSIN and STATTIC commonly inhibited pro-atherogenic target genes, which was upregulated in atherosclerotic plaques in the aortas of high-fat diet-fed ApoEKO mice and associated with inflammation, proliferation, adhesion, chemotaxis, and response to lipids. Interestingly, the majority of these genes could be linked to macrophage subtypes present in aortic plaques in HFD-fed LDLR-KO mice. Together, this suggests that ALEKSIN represents a novel class of multi-IRF inhibitors, which inhibits IRF-, STAT-, and NF-κB-mediated transcription and could offer great promise for the treatment of CVDs. Furthermore, the ALEKSIN and STATTIC commonly inhibited pro-inflammatory gene signature could help monitor plaque progression during experimental atherosclerosis.